Подготовка будущих психологов к практической деятельности тренера социально-психологического тренинга методом игрового проектирования - Попова, Галина Викторовна; Милорадова, Наталья Эдуардовна (НТУ "ХПИ", 2012)
In the article practice of the use of method of the playing planning is described at teaching of future psychologists to concrete skills of work of trainer. The stages of leadthrough and methods of organization of the thematic playing planning are described. The methodical receptions of development of creative thought, activations of participation of students, are offered in the playing planning. Possibilities of method come into question in-process, got results of looking after strategy of participation of students in playing practice on creation of the training programs. A list over of concrete competenses which students seize during playing practice is brought.
Keywords: метод инцидента; мозговая атака; деловые игры; метод погружения; игровое проектирование